DYNAMIC MODELING AND SURFACE INTEGRITY OPTIMIZATION OF LOW-FREQUENCY HYDRAULIC IMPULSE SYSTEMS - Smakova, N.; Pankov, S.; Baisadykov, B.; Zelenkov, V.; Toibazarov, D.; Karypov, A.A. (Eurasian Physical Technical Journal, 2026)
This study investigates the dynamic behavior and surface integrity optimization of low-frequency hydraulic impulse systems operating under cyclic loading conditions. Particular attention is paid to the performance of the hydraulic module rod, which is subjected to repeated dynamic impacts during system operation. The influence of surface roughness, residual stresses, and microhardness on vibration stability and durability of friction pairs is analyzed. A dynamic mathematical model describing pressure variation, piston motion, and energy transfer within the hydraulic impulse chamber is developed. The model is implemented in the MATLAB/Simulink simulation environment for numerical analysis of transient processes. Experimental studies were conducted on cylindrical rod-type specimens made of 30KhGSA alloy steel processed using rotary multi-blade turning technology. The experimental results demonstrate that optimization of machining parameters significantly improves surface quality and reduces vibration amplitude of the hydraulic impulse system. The proposed modeling approach enables prediction of system dynamic behavior and provides a basis for improving operational stability. The obtained results confirm that the integration of advanced machining technologies with digital modeling tools can increase the reliability and efficiency of hydraulic impulse systems used in industrial applications.